Reading Transition with Suspicion: An Affective Critique of Umwandlung in N. O. Body’s Aus eines Mannes Mädchenjahren and Its Reception - Meier-Brix, Orlando (SQS – Suomen Queer-tutkimuksen Seuran lehti, 2023)
This article analyses Umwandlung (gendersex transition) as a sexological and autobiographic narrative in “N. O. Body’s” (Karl M. Baer’s) memoir Aus eines Mannes Mädchenjahren (1907), one of the first self-authored accounts of an intersex person in modern times. Scholars as well as authors of popular queer and trans genealogies frame Baer’s transition through medical intervention, although the historical evidence suggests otherwise. This discrepancy generates the author’s suspicion, which functions as a reading strategy and an affective methodology. The article pursues two central arguments: Empirically, it argues to de-medicalize Umwandlung as an early 20th century concept of transition via the example of Karl M. Baer’s memoir. Methodologically, it reintroduces suspicion to affect theory and proposes “reading with suspicion” as affective strategy to critically engage with trans and intersex narratives. Ultimately, the article argues that a more nuanced, complex and contradictory perspective on Umwandlung not only gives new insight into early 20th century intersex and trans history but also offers potential alternatives to contemporary medicalizing concepts of transition. In order to do so, the article proposes an interdisciplinary framework comprised of literary analysis as well as historiographic source study and conceptual history within the fields of trans studies and intersex studies. Keywords: Intersex history, autobiography, early 20th century sexology, German, transition narratives, Karl M. Baer, Magnus Hirschfeld, critique, post-critique, suspicion